Comparison of Intrauterine Suitable Balloon and Foley Balloon in the Prevention of Adhesion after Hysteroscopic Adhesiolysis. (8th November 2018) - Zhu, Ru; Duan, Hua; Gan, Lu; Wang, Sha
Abstract : Objective . To compare the effect of intrauterine suitable balloon (ISB) and Foley balloon (FB) in the prevention of adhesion after hysteroscopic adhesiolysis in patients with intrauterine adhesions (IUAs). Methods . A retrospective study was conducted on 150 women with moderate and severe IUAs, who underwent hysteroscopic adhesiolysis. According to the postoperative placement of the ISB or FB, the cohort was divided into the ISB group and the FB group. A second-look hysteroscopy was performed at 3 months postsurgery. The scoring system proposed by the American Fertility Society (AFS) was used to evaluate the adhesion during hysteroscopy. Subgroup analysis was carried out based on the degree of IUAs. Results . (1) In the ISB group, only 25% (19/76) women presented adhesion reformation after surgery, while, in the FB group, the adhesion reformation was observed in 35.1% (26/74) patients; however, the difference was not statistically significant ( P >0.05). Subsequently, the adhesion reformation rate (29.5%, 13/44) after surgery with an ISB for severe intrauterine adhesions was significantly lower as compared to that (53.6%, 15/28) with FB ( P <0.05). (2) In the ISB group, the reduction in the adhesion score after surgery was 8 points, which was significantly higher than the 7 points in the FB group ( P <0.05). Conclusion . The ISB is better than the FB in preventing the adhesion reformation and reducing the AFS score after hysteroscopic adhesiolysis in severe IUAs . Also, it can effectively prevent the adhesion reformation in severe IUAs with a similar effect on moderate IUAs.